2005
DOI: 10.1016/j.chemosphere.2004.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of microcystins in aqueous solution with in situ electrogenerated active chlorine

Abstract: A new and efficient method for the degradation of microcystins (one family of blue algal toxins) was developed and studied. Microcystins (MCs) in water were directly and effectively removed by active chlorine transformed in situ from the naturally existing Cl À in water resource using electrochemical method. , 20°C and pH 7.00. The qualitative analysis showed that the heptapetide ring and the Adda group of both treated MCs were changed. The results also indicated that the removal rates of both MCs increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Microcystis bloom caused a wide range of social, environmental, and economic problems, such as deterioration of water quality, decrease of the esthetic value of the affected water, and damage of aquaculture industries (Lam et al 1995;Briand et al 2003;Shi et al 2005). In particular, the blooms of Microcystis aeruginosa have caused heavy damages in recent years in China (Guo 2007;Xu et al 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Microcystis bloom caused a wide range of social, environmental, and economic problems, such as deterioration of water quality, decrease of the esthetic value of the affected water, and damage of aquaculture industries (Lam et al 1995;Briand et al 2003;Shi et al 2005). In particular, the blooms of Microcystis aeruginosa have caused heavy damages in recent years in China (Guo 2007;Xu et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Microcystin-LR (MC-LR) has been shown to be a liver-tumor promoter (Humpage and Falconer 1999). Besides decreasing the pollution and recovering the ecological environment of affected lakes and ponds, many other approaches including physical, chemical, and biological methods have been developed to control cyanobacterial pollution in emergencies (Fallon and Brock 1979;Nagasaki et al 2004;Shi et al 2005;Mazur-Marzec et al 2006). Most of these approaches cannot be practically applied to remediate cyanobacterial-polluted water bodies completely because of their negative effects on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the addition of chloride ions in the electrolyte can increase the electrooxidation removal efficiency of many pollutants such as 2-naphthol, urea and microcystins [15][16][17]. In the case of EDTA, it was reported that in situ generated active chlorine allowed the decomplexation of metal-EDTA, which was beneficial to the metal recovery [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore not surprising that conventional drinking water treatments have only limited efficacy in removing dissolved MC (Svrcek & Smith 2004). Many studies have been conducted to solve this important trouble during the last years (Chen et al 2005;Jurczak et al 2005;Qiao et al 2005;Shi et al 2005;Svrcek & Smith 2004).…”
Section: Introductionmentioning
confidence: 99%